Features of the behavior of 4-amino-5-carboxamido-1,2,3-triazole in multicomponent heterocyclizations with carbonyl compounds - Gladkov, Eugene S.; Gura, Katerina A.; Sirko, Svetlana M.; Desenko, Sergey M.; Groth, Ulrich; Chebanov, Valentin A. (Beilstein Journal of Organic Chemistry, 2012)
Multicomponent reactions involving polyfunctional 4-amino-5-carboxamido-1,2,3-triazole and cyclic carbonyl-containing CH-acids were studied under conventional thermal heating, microwave and ultrasonic irradiation. The features of the reactions studied were discussed and the optimized procedures for the synthesis of final triazolopyrimidines were elaborated. In contrast to the similar MCRs of numerous other aminoazoles, a change of direction of the heterocyclizations in the case of 4-amino-5-carboxamido-1,2,3-triazole was not observed when microwave or thermal heating was substituted by ultrasonication at ambient temperature.
Keywords: 4-amino-5-carboxamido-1,2,3-triazole; heterocycle; microwave-assisted synthesis; multicomponent reaction; ultrasound-assisted synthesis